PENGARUH JARAK TERHADAP INTERVAL WAKTU PERUBAHAN SUHU PERMUKAAN BETON PADA UJI THERMOGRAPHY AKTIF - K, Suyadi K; Setio, Herlien D; S, Adang; Z, Ediansjah (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2020)
Concrete surface temperature changes on active thermography testing process using a halogen lamp will occur in a relatively short time. These changes are very useful in the image interpretation process which relies on changes in thermal contrast to determine the internal conditions of reinforced concrete. This research aims to determine the time interval dominance concrete surface temperature changes due to changes in object distance to the heat source as the excitation source of heat. Tests carried out in the room, so that the concrete surface temperature changes due to the effects of wind are considered small. Measurement of the temperature of the concrete surface due to the heating and cooling process using thermocouples and thermography methods. Halogen lamps are used as a source of heat excitation placed at various distances (dobj), namely 20 cm; 30 cm and 40 cm. The distance between the halogen lamp axles in this study was 30 cm. The dimensions of the test object were used 10 cm x 10 cm x 15 cm with a concrete quality of 20 MPa. The frequency percentage is analyzed according to the amount of data with the same time interval for the change in surface temperature at each distance of the specimen from the heat source. The results showed that the change in the distance of the specimen to the heat source up to 40 cm had a quite small difference, but the increase in the distance between the test object and the heat source tended to decrease the dominance of changes in the temperature of the concrete surface. The average dominance of changes in the temperature of the concrete surface is almost above 75% of the temperature change occurs at the smallest interval of the measuring instrument used, namely 1 second using a thermocouple and 0,133 seconds using the thermography method. The highest percentage shows that changes in surface temperature often occur in the range of time intervals. So based on this analysis without reviewing aspects of the distribution pattern of the data, can be concluded that the surface temperature testing of concrete by using active thermography in the room had to use measuring devices that can record temperature changes every interval of 0.133 seconds. This shows that the change in the temperature of the concrete surface during active thermography testing, the setting of the test instrument for measuring temperature changes is used in that time interval.